2017
DOI: 10.1177/1010428317722064
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A expression predicts recurrences of tamoxifen-treated breast cancer

Abstract: CIP2A is emerging as an oncoprotein overexpressed commonly across many tumours and generally correlated with higher tumour grade and therapeutic resistance. CIP2A drives an oncogenic potential through inhibiting protein phosphatase 2A, stabilizing MYC, and promoting epithelial-to-mesenchymal transition, although further biological mechanisms for CIP2A are yet to be defined. CIP2A protein expression was studied by immunohistochemistry in oestrogen receptor-positive primary breast cancers (n = 250) obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Furthermore, a significant association was observed between high CIP2A expression and HER-2 positivity, ER and PR negativity. Many studies reported association of high CIP2A expression with poor prognostic factors [36,37,38,39] and recurrence after treatment [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a significant association was observed between high CIP2A expression and HER-2 positivity, ER and PR negativity. Many studies reported association of high CIP2A expression with poor prognostic factors [36,37,38,39] and recurrence after treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of CIP2A overexpression as a prognostic marker has been established in various solid and hematological malignancies, including, chronic myelogenous leukemia, bladder carcinoma, non-small cell lung cancer, multiple myeloma, and endometrioid adenocarcinoma [13,14,15,16,17]. Regarding breast cancer, CIP2A expression has been correlated with aggressiveness and also predicts a worse prognosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the clinical level, CIP2A overexpression hasbeen reported to predict poor outcome in breast cancer [ 12 , 25 ], with a special relevance in the TN subtype [ 26 , 27 ]. Moreover, CIP2A expression has also been described as a predictive marker of recurrence in tamoxifen-treated breast cancer patients [ 28 ]. The high relevance of the CIP2A/AKT interplay has been largely reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined that the levels of this protein are over-expressed in human breast cancer tissues, so its presence allows the diagnosis and prognosis of breast cancer, therefore it is useful as a diagnostic marker for this disease, in addition to being detectable in blood, which gives it greater value, as it is easily detectable [3,4]. It has been found that tamoxifen-induced apoptosis in breast cancer is associated with the down-regulation of CIP2A and p-AKT, likewise the membranous expression of CIP2A is significantly higher in patients with tamoxifen resistance, however the mechanism by which resistance is generated is not yet fully glimpsed [35].…”
Section: Cancerous Inhibitor Of the Protein Phosphatase 2a (Cip2a)mentioning
confidence: 99%
“…Membranous CIP2A is an indicator of resistance to tamoxifen in breast cancer with positive hormone receptors. It is considered that it may be useful to select patients with positive estrogen receptor at risk of developing resistance to tamoxifen [35].…”
Section: Cancerous Inhibitor Of the Protein Phosphatase 2a (Cip2a)mentioning
confidence: 99%